(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, the Soviet-Afghan international archaeological expedition, which has been conducting large-scale research since the second half of the last century, divides the archaeological and architectural monuments of Balkh and its surroundings into several oases depending on their location. Information about learning is provided.